Classical Quantum Hidden Variable Gravitation - Bender, Darrell (European Journal of Applied Sciences, 2024)
Years ago, just by thinking about it, we discovered the rate of a unit clock in a gravitational field, and, after that, because of the slower clock rate in a gravitational field, that the energy that an energy wave sphere loses becomes its energy of motion. We calculated the radius of a proton energy wave sphere contained in an electron energy wave sphere. We extend the concept of energy wave spheres to imaginary energy wave spheres to explain the change in frequency of the wave in an energy wave sphere. We show that a black hole is an imaginary energy wave sphere with radius alpha and wave velocity ic, which gives the nature of the kernel with radius alpha of a mass M. We show that the radial component of the velocity of a light ray, perpendicular to a radius in a gravitational field, has the velocity of an imaginary energy wave sphere inside the photon. We did not come here to offer a false theory, but, rather, a look through the veil of gravitation. We are the looking glass. A light ray with constant velocity -c moving toward the imaginary kernel of a mass M along a radius has a real energy wave sphere with wave velocity 0 always. In the face of imaginary energy wave spheres along its path, the wave velocity of the energy wave sphere never becomes imaginary assuming any energy lost by the wave goes into the velocity of the energy wave sphere. Taking this non-imaginary wave velocity clue amounts to assuming it holds for all real energy wave spheres and, as a consequence, that the absolute velocity of a real energy wave sphere cannot exceed c. Knowing that the source of this velocity is the energy wave sphere itself, we should have already concluded this anyway. As for a real kernel for the mass M for some radius less than alpha, no real energy wave sphere has an imaginary energy wave sphere to hold it together for such a radius. The only conceivable place to match the wave velocity of the real kernel of a mass M, where the wave velocity of the kernel is c and the velocity of the energy wave sphere, not its wave velocity, is -c, is at the radius alpha, thus extending the notion of a black hole to include this real energy wave sphere.